WARIA DAN UPAYANYA DALAM MERAIH KAPITAL SIMBOLIK: STUDI KASUS PENGAJIAN AL-IHKLAS DAN PERSEKUTUAN DOA HATI DAMAI DAN KUDUS - Lastiko Endi Rahmantyo (Lakon : Jurnal Kajian Sastra dan Budaya, 2014)
Transgender and religion have always been two contradictory things called as oxymoron. All religions do not admit the discourse of transgender and it does happen in Surabaya. The discrimination and stigma attached to them have made them avoid the religious places. It is the notion happening in most of transgender because they are shy and felt that they did not belong to it. Interestingly, there were two religious affiliations created and addressed for transgender in Surabaya: Pengajian Al-Ikhlas (for Moslems) and Persekutuan Doa Hidup Damai dan Kudus (for Christians). By the time this thesis was finished, the two religious organizations have already grown up for more than ten years and still exist and keep developing. The theory used in this thesis was Pierre Bourdieu’s Habitus, Field, and Capital. It was used to analyse how those two affiliations were built and developed. The method used was qualitative method by using ethnographic research. The primary data used were the data from the interviews and participatory observation; while the secondary data were from documents such as newspapers and magazines. The results of this thesis indicated that the Habitus owned and internalized by the owner of these affiliations were the major reason on why these affiliations were grown and developed. It was also facilitated by the field in Surabaya that made them comfortable. Furthermore, capital was also noted to be the one that keeps the affiliations running. The attendants were having extra care within their death, extra cash, socialization, and also the most important was being recognized as citizens.